Light-triggered evolution of molecular clusters toward sub-nanoscale heterojunctions with high interface density. Issue 56 (26th June 2019) - Xue, Chaozhuang; Zhang, Jiaxu; Wang, Xiang; Gu, Meng; Zhu, Yuanmin; Li, Dong-Sheng; Guo, Jun; Liu, Yang; Wu, Tao
Abstract : Pyridine-capped Zn–S–O molecular clusters are light-triggered into sub-nanoscale ZnS/ZnO heterojunctions with highly rich interfaces. Abstract : Herein, we report a simple, yet highly effective approach for constructing a new type of sub-nanoscale ZnS/ZnO heterojunction (∼2–4 nm) with highly rich interfaces by photoetching hybrid Zn–S–O molecular clusters. The obtained ZnS/ZnO heterojunctions with ZnS spheres decorated with ultrasmall amorphous ZnO dots exhibit superior photocatalytic performance (∼94.0 μmol g −1 h −1 ), compared to nanoscale homologous samples obtained via conventional heat treatment (∼17.0–21.4 μmol g −1 h −1 ). Such a light-triggered molecular-cluster-to-heterojunction strategy provides a synthetic approach to building other sub-nanoscale hetero-structured materials for further promoting the catalytic-related applications.